Search for new phenomena in monophoton final states in proton-proton collisions at root s=8 TeV - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Bergauer, T.; Dragicevic, M.; Eroe, J.; Friedl, M.; Fruehwirth, R.; Ghete, V. M.; Hartl, C.; Hoermann, N.; et al. (Elsevier B.V., 2016)
Results are presented from a search for new physics in final states containing a photon and missing transverse momentum. The data correspond to an integrated luminosity of 19.6 fb(-1) collected in proton-proton collisions at root s = 8 TeV with the CMS experiment at the LHC. Nodeviation from the standard model predictions is observed for these final states. New, improved limits are set on dark matter production and on parameters of models with large extra dimensions. In particular, the first limits from the LHC on branon production are found and significantly extend previous limits from LEP and the Tevatron. An upper limit of 14.0 fb on the cross section is set at the 95% confidence level for events with a monophoton final state with photon transverse momentum greater than 145 GeV and missing transverse momentum greater than 140 GeV. (C) 2016 CERN for the benefit of the CMS Collaboration. Published by Elsevier B.V.
Keywords: CMS; Physics; Monophoton; Dark matter